2021
DOI: 10.1016/j.ajogmf.2020.100272
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of both complex and isolated cases of infants with large stomach on fetal ultrasound

Abstract: BACKGROUND: A sonographically large fetal stomach has been associated with gastrointestinal obstruction, per case reports, and is often followed up with serial ultrasound examinations. The frequency of this phenomenon has not been systematically studied, resulting in challenges in counseling parents about the prognosis and making cost-benefit analysis of serial ultrasound follow-up difficult to assess. OBJECTIVE: This study aimed to determine the frequency at which an enlarged fetal stomach as the sole abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In addition, there is some discrepancy between the fetal gastric growth and overall fetal growth throughout pregnancy, as evidenced by the fact that the correlation coefficient of the gastric surface area with gestational age is lower than that of the fetal biparietal diameter with gestational age. This is further supported by the rising standard deviation of average stomach size with gestational age (15) .…”
Section: Discussionmentioning
confidence: 68%
“…In addition, there is some discrepancy between the fetal gastric growth and overall fetal growth throughout pregnancy, as evidenced by the fact that the correlation coefficient of the gastric surface area with gestational age is lower than that of the fetal biparietal diameter with gestational age. This is further supported by the rising standard deviation of average stomach size with gestational age (15) .…”
Section: Discussionmentioning
confidence: 68%
“…This is supported by McCormick et al, who prospectively examined the finding of an unusually large stomach in routine prenatal ultrasound. They found that only 0.62% of isolated large fetal stomachs pointed to gastrointestinal anomalies, thus concluding that an isolated large stomach seems to be an incidental finding not suggestive of intestinal anomaly [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, an enlarged stomach can also be a normal variant (Figure 12A). 57 However, a larger than normal stomach can be found in cases of pyloric, duodenal, and intestinal obstructions (Figure 12C-E). 58 Pyloric stenosis or atresia is a very rare cause of gastric outlet obstruction in the fetus; however, hypertrophic pyloric stenosis is a frequent cause of upper gastrointestinal obstruction and persistent vomiting in the neonate.…”
Section: Group Iii: Abnormal Shape/enlargement Of Stomach Umbilical V...mentioning
confidence: 98%